Plio/Pleistocene stable isotopes (δ13C and δ18O) of benthic foraminifera (Uvigerina spp., C. wuellerstorfi, M. barleanum) of core SO264_53-2 (Minnetonka Seamount) - Dirk Nürnberg; Nadine Gehre; Sebastian Fessler (PANGAEA, 2025)
Sediment cores from the volcanic Emperor Seamount Chain obtained during RV SONNE cruise SO264 (SONNE-EMPEROR) in August 2018 allow us to reconstruct lateral changes in the subarctic and subtropical gyres in the pelagic North Pacific over the last ~3.4 million years. This dataset comprises benthic stable carbon (δ13C) and oxygen isotope (δ18O) data from gravity core SO264_53-2, which was recovered from Minnetonka Seamount (47°38.931 N 169°20.417 E) from 2325 m water depth. Measurements were performed on the benthic foraminiferal species Uvigerina spp., Cibicidoides wuellerstorfi, and Melonis barleanum. Sampling and analytical studies were carried out from 0.005–8.605 m core depth at ~2 cm spatial resolution. The isotope analyses were performed on a Thermo Scientific MAT 253 mass spectrometer with an automated Kiel IV carbonate preparation device.